2016
DOI: 10.3390/ijms17101640
|View full text |Cite
|
Sign up to set email alerts
|

An Inflammatory Nucleus Pulposus Tissue Culture Model to Test Molecular Regenerative Therapies: Validation with Epigallocatechin 3-Gallate

Abstract: Organ cultures are practical tools to investigate regenerative strategies for the intervertebral disc. However, most existing organ culture systems induce severe tissue degradation with only limited representation of the in vivo processes. The objective of this study was to develop a space- and cost-efficient tissue culture model, which represents degenerative processes of the nucleus pulposus (NP). Intact bovine NPs were cultured in a previously developed system using Dyneema jackets. Degenerative changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 71 publications
(95 reference statements)
2
26
0
Order By: Relevance
“…These results indicate that the current model may mimic a “degenerative”, while not “degenerated” IVD condition. To simulate a degenerated IVD with loss of ECM content, longer term culture or enzyme injection (Chan, Burki, Bonel, Benneker, & Gantenbein‐Ritter, ; Jim, Steffen, Moir, Roughley, & Haglund, ; Krupkova et al, ) would be needed to deplete the ECM components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that the current model may mimic a “degenerative”, while not “degenerated” IVD condition. To simulate a degenerated IVD with loss of ECM content, longer term culture or enzyme injection (Chan, Burki, Bonel, Benneker, & Gantenbein‐Ritter, ; Jim, Steffen, Moir, Roughley, & Haglund, ; Krupkova et al, ) would be needed to deplete the ECM components.…”
Section: Discussionmentioning
confidence: 99%
“…Several proinflammatory degenerative culture systems have been developed using explant/organ culture (Walter, Likhitpanichkul, et al, ; Krupkova et al, ; Ponnappan et al, ; Purmessur et al, ; Teixeira et al, ). Though, many studies lack the 3D micro‐environment of the IVD and/or cyclic dynamic loading condition, and therefore might fail to represent relevant biological and biomechanical alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of TNF‐α aggravates the NPCs senescence by promoting levels of senescence markers p53 and p16 . TNF‐α also disturbs the balance between synthesis and degradation of ECM by up‐regulating MMP‐3, MMP‐13 and ADAMTS‐4, as well as down‐regulating aggrecan and collagen II . Moreover, it is widely recognized that TNF‐α induces mitochondrial dysfunction by increasing ROS production, which may further aggravate senescence and ECM catabolism in NPCs .…”
Section: Introductionmentioning
confidence: 99%
“…6 TNF-α also disturbs the balance between synthesis and degradation of ECM by up-regulating MMP-3, MMP-13 and ADAMTS-4, as well as down-regulating aggrecan and collagen II. 7 Moreover, it is widely recognized that TNF-α induces mitochondrial dysfunction by increasing ROS production, [8][9][10] which may further aggravate senescence and ECM catabolism in NPCs. 11,12 From these studies, it is obvious that maintaining mitochondrial homeostasis would help to reverse senescence and ECM degradation in NPCs against IVDD.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that in vitro organ cultures can be more suitable than cells to study IVD biology and therapeutic testing as they retain biological and biomechanical properties similar to the IVD in vivo . However, hallmarks of IVD degeneration are usually not present in organ cultures and have to be induced by nonphysiological insults like injections of proteases or high concentrations of proinflammatory cytokines . Generating organ cultures with multiple edited genes (aggrecan, collagen, MMPs, ADAMTS, ILs) might simulate IVD pathologies more naturally.…”
Section: Targeted Genome Editing By Crispr/cas9mentioning
confidence: 99%